2020
DOI: 10.3390/w12030634
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Terracing as Optimization of Controlled Slope Intervention

Abstract: With the introduction of mechanization in agriculture, the area of terraced slopes has increased. However, in most cases, the planning of terracing in practice remains experience-based, which is no longer effective from an agricultural, geological, and hydrological point of view. The usual method of building terraces, especially terraces with earth risers, is therefore outdated, and a new method must be found for planning and building terraced areas. In addition to geographical information system (GIS) tools, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…According to Hudson (1981), the slope angle exceeding 30° is a key limiting factor for the construction of bench terraces. Even in stable and deep soils, higher slope angles increase the water pressure in the soil pores and might initiate the riser collapse (Berčič & Ažman‐Momirski, 2020). Bugenimana et al (2019) found in Rwanda that most of the terraced sites do not follow the technical guidelines, whereas many zones were built with slope angles lower or higher than standards and claim that such circumstances have increased the risks of landslide and erosion with no clear advantage for soil erosion mitigation and crop production.…”
Section: Discussionmentioning
confidence: 99%
“…According to Hudson (1981), the slope angle exceeding 30° is a key limiting factor for the construction of bench terraces. Even in stable and deep soils, higher slope angles increase the water pressure in the soil pores and might initiate the riser collapse (Berčič & Ažman‐Momirski, 2020). Bugenimana et al (2019) found in Rwanda that most of the terraced sites do not follow the technical guidelines, whereas many zones were built with slope angles lower or higher than standards and claim that such circumstances have increased the risks of landslide and erosion with no clear advantage for soil erosion mitigation and crop production.…”
Section: Discussionmentioning
confidence: 99%
“…Berčič, and Ažman-Momirski [16] developed an innovative parametric design procedure for planning the design of terraced landscapes, with a case study in Slovenia, implemented in the "Grasshopper" plugin in Rhino 3D. The approach proposed was proven to be effective in optimizing the design process of new terraced systems.…”
Section: Overview Of the Special Issuesmentioning
confidence: 99%
“…Such kinds of research efforts could be considered of particular interest, since, while most of the "historical" terraced landscapes were created a long time ago, they offer the possibility of analyzing the different parts of the terracing implementation, highlighting possible errors, their consequences, but also innovative design methodologies. Some of the case studies focused on issues related to terrace abandonment (Figure 3) [13,15,17,19,20], which represent an issue at the global scale [1,6,7], while others focused instead on new terrace system implementation [14,16]. Such kinds of research efforts could be considered of particular interest, since, while most of the "historical" terraced landscapes were created a long time ago, they offer the possibility of analyzing the different parts of the terracing implementation, highlighting possible errors, their consequences, but also innovative design methodologies.…”
Section: Final Remarks and Future Perspectivesmentioning
confidence: 99%